Correlation between the Dynamics of Nanoconfined Water and the Local Chemical Environment in Calcium Silicate Hydrate Nanominerals. Issue 44 (17th June 2021) - Musumeci, Valentina; Goracci, Guido; Sanz Camacho, Paula; Dolado, Jorge S.; Aymonier, Cyril
Abstract: Calcium silicate hydrates are members of a large family of minerals with layered structures containing pendant CaOH and SiOH groups that interact with confined water molecules. To rationalize the impact of the local chemical environment on the dynamics of water, SiOH‐ and CaOH‐rich model nanocrystals were synthesized by using the continuous supercritical hydrothermal method and then systematically studied by a combination of spectroscopic techniques. In our comprehensive analysis, the ultrafast relaxation dynamics of hanging hydroxy groups can be univocally assigned to CaOH or SiOH environments, and the local chemical environment largely affects the H‐bond network of the solvation water. Interestingly, the ordered "ice‐like" solvation water found in the SiOH‐rich environments is converted to a disordered "liquid‐like" distribution in the CaOH‐rich environment. This refined picture of the dynamics of confined water and hydroxy groups in calcium silicate hydrates can also be applied to other water‐containing materials, with a significant impact in many fields of materials science. Abstract : Xonotlite and tobermorite minerals are characterized by layered structures containing pendant CaOH and SiOH groups that interact with confined water molecules. In these systems, the hydrogen‐bond network and the dynamics of confined water are modified by the presence of different chemical environments. Herein, is shown that the ordered "ice‐like" distribution of water molecules found in the SiOH‐rich environments, as in tobermorite, is converted to a disordered "liquid‐like" distribution in the CaOH‐rich environment in xonotlite.